2001
DOI: 10.4315/0362-028x-64.9.1399
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Aquacultured Freshwater Fish Portions in Prepackaged Trays Stored at 3°C

Abstract: Fresh trout fillets and salmon slices packed in trays were obtained from two multinational chain supermarkets and evaluated for freshness and bacteriological quality immediately after packaging and during storage at 3 degrees C. Initial aerobic counts at 30 and 25 degrees C were significantly (P < 0.05) lower in trout fillets (5.27 +/- 0.57 and 4.87 +/- 0.80 log CFU/g, respectively) than in salmon slices, where levels in excess of 6 log CFU/g were found. In both products, initial Enterobacteriaceae counts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 10 publications
4
12
0
1
Order By: Relevance
“…[36]. These values obtained in this study are close to the values reported earlier for aquacultured fresh trout from Spain [37,41], Greece [38,39] and U.K [40]. It is widely accepted that the initial microbial load of fresh water varies depending on water conditions and temperature.…”
Section: Resultssupporting
confidence: 78%
“…[36]. These values obtained in this study are close to the values reported earlier for aquacultured fresh trout from Spain [37,41], Greece [38,39] and U.K [40]. It is widely accepted that the initial microbial load of fresh water varies depending on water conditions and temperature.…”
Section: Resultssupporting
confidence: 78%
“…In their study on fish fillets, González-Rodríguez et al [8] used the Enterobacteriacea counts as an indicator and stated that when the count exceeded 6 log cfu/g the fish quality was unacceptable. In their study Chytiri et al [11] found that Enterobacteriaceae was a part of the spoilage microflora of filleted trout and reached a level of 5.5 log CFU/ cm 2 when stored on ice.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic positive colonies (black with halo) were confirmed to be S. aureus by the API ® Staph and were coagulase positive. Neither isolate produced the classical food poisoning enterotoxin types A, B, C, D or E. In their report surveying 24 lots of freshwater fish, González-Rodríguez et al [8] reported 4 confirmed isolates of S. aureus. They did not determine if these isolates were enterotoxin producers, but did determine that most of the isolates were coagulase-and thermonuclease negative.…”
Section: The Baxmentioning
confidence: 98%
See 1 more Smart Citation
“…Güney Hindistan'da balıkların avlandığı sulara kanalizasyon suları ve kuş dışkılarının karışması, balıkların taşınması sırasında kullanılan buzun ucuz ve düşük kalitede olması, hijyenik olmayan ellerle balıkların kasalara yerleştirilmesi, kontamine su ile balıkların ıslatılması ve sineklerin yoğun olması nedeniyle Salmonella'nın prevalansının oldukça yüksek olduğu görülmüştür (16).…”
Section: Katı Besiyerine Ekimunclassified